Analysis of drug interactions at the end of life. Issue 3 (17th April 2015) - Morgan, N A; Rowett, D; Currow, D C
Abstract : Background: As death approaches, patients are at their most frail, but an increasing symptom burden often necessitates an increase in medications, putting them at higher risk for drug–drug interactions. Objectives: To assess the potential for drug–drug interactions in routine prescribing at the end of life. Methods: An Australian retrospective multicentre case-note review of 266 consecutive adult patients who were referred to specialist palliative care, with data available on 166. Medications used in the last 2 weeks of life were screened for potential interactions using the 'Stockley's Drug Interactions' software. Results: The mean number of medications prescribed was 10.8, median 9 (IQR 6–14); all patients received at least one medication. In this study, 72% of patients were at risk of 1 or more potential drug–drug interaction. The mean number of potential interactions was 4.4, with a median of 2.5 (IQR 0–7) per patient. There were only 4/166 (2.4%) prescribed medications with an associated clinical record of an adverse drug reaction. Conclusions: Potential drug–drug interactions are common for this group of patients. Some interactions may be recognised as an acceptable risk when the prescription is written. Further research is necessary to determine the best way to improve recognition of potential drug–drug interactions and the rates of morbidity or accelerated mortality associated with this. It is likely that palliative care services will need to implement multiple strategies including greater use of computerised prescribing software, and greater closer liaison with clinical pharmacists.